The Photography as a Life’s Diary - Carmen Menéndez (Arteterapia)
An experience that took place in Paraguay is presented. In a home for mother-child intrafamiliar abuse victims. The work has been developed basically through photography. It shows a particular life experience due to the characteristics of the group, the cultural and social distances and the focus and time limit of the art therapy course. The objectives of the course, the development and the reflection upon photography, as a therapeutic medium, will be described.